2021
DOI: 10.1002/cctc.202100412
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Formylation of Nitroarenes using HCOOH over Bimetallic C−N Framework Derived from the Integration of MOF and COF

Abstract: CoZn embedded CÀ N framework is prepared by the carbonization of CoZn containing MOF integrated with COF porous architecture in Ar atmosphere. The graphitic nature of porous carbon is confirmed from Raman analysis. The porosity and nanostructure information are retrieved from N 2 -sorption and transmission electron microscopic analysis, respectively. The incorporation of different metals and their oxidation states and types of nitrogen present in the CÀ N framework are confirmed from X-ray photoelectron spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…It signifies that TBCN@3%rGO contains moderate and strong basic sites, where CO 2 chemisorption takes place. 57,58 This basicity distribution arises due to the "N" surroundings in the triazine moieties of TBCN@3%rGO, which are effectively involved in the deprotonation of alcohols and promote their complexation on the surface of TBCN@3% rGO. 59 Moreover, the NH 3 -TPD profile in Figure 6b shows a weak desorption signal around 150 °C and a broad NH 3 desorption signal from 300 to 550 °C.…”
Section: Light Absorption Properties and Flat Band Positions (Uv And ...mentioning
confidence: 99%
“…It signifies that TBCN@3%rGO contains moderate and strong basic sites, where CO 2 chemisorption takes place. 57,58 This basicity distribution arises due to the "N" surroundings in the triazine moieties of TBCN@3%rGO, which are effectively involved in the deprotonation of alcohols and promote their complexation on the surface of TBCN@3% rGO. 59 Moreover, the NH 3 -TPD profile in Figure 6b shows a weak desorption signal around 150 °C and a broad NH 3 desorption signal from 300 to 550 °C.…”
Section: Light Absorption Properties and Flat Band Positions (Uv And ...mentioning
confidence: 99%
“…† The Co 2p 3/2 of Co@N-C was deconvoluted into three peaks that appeared at 778.3 eV, 780.4 eV, and 784.5 eV corresponding to metallic Co, Co-N, and a satellite peak, respectively. 38 Similarly, Co 2p 1/2 can be deconvoluted at 794.1 eV attributed to the Co 0 (Fig. 2a).…”
Section: Resultsmentioning
confidence: 87%
“…The carbonized catalysts exhibited the graphitic band (G band) at 1585.2 cm −1 , corresponding to the in-plane vibration of sp 2 carbon atoms, and a disorder band (D band) at 1324.3 cm −1 representing the nonperfect crystalline structure of the material due to the N doping in the framework. 38 The intensity ratio of the D band and G band (I D /I G ) for Co 1−x -Pd x @N-C catalysts was higher than that of Co@N-C and Pd@N-C (Fig. S1 †).…”
Section: Resultsmentioning
confidence: 96%
“…11,12 Thus far, several studies have been reported on the one-pot synthesis of N-formamides from nitroarenes using HCOOH or its derivatives. 5,[13][14][15][16] Given the fact that a selective decomposition of HCOOH to H 2 + CO 2 and the use of CO 2 as a formylation source thermodynamically are feasible (ΔG 298K = −35 kJ mol −1 ), it requires activation energy, which is generally provided through thermal energy and a suitable catalyst. 17,18 However, using light energy as an energy source is a much more sustainable process and can answer the energy crisis and mitigate environmental threats.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Thus far, several studies have been reported on the one-pot synthesis of N -formamides from nitroarenes using HCOOH or its derivatives. 5,13–16…”
Section: Introductionmentioning
confidence: 99%